How much did the maize export ban cost Malawi? - Gondwe, Anderson; Baulch, Bob (International Food Policy Research Institute, 2017)
This note has been prepared by IFPRI Malawi at the request of the UK Department for International Development (DFID) and the United States Agency for International Development Malawi (USAID), and estimates how much export revenue Malawi has lost due the export ban on maize during the summer/autumn of 2017. Using three potential export locations in East Africa, transportation costs to these locations from central Malawi, and two alternative estimates of Malawi’s likely maize surplus, this note estimates that Malawi lost between MWK 25 billion and MWK 69 billion (approximately $34 to $95 million) from the export ban in the 2016/17 agricultural year.